Influence of Distribution Strategy on Microinsurance Uptake among Micro and Small Enterprises in Nairobi City County, Kenya - Mulumbi, Aggrey; Onjure, Caleb; Muriithi, Jane (International Journal of Modern Risk Management, 2025)
Purpose: The study aimed to investigate influence of distribution strategies on microinsurance uptake among micro and small enterprises in Nairobi County, Kenya. Methodology: The study used a descriptive research methodology and positivist mindset. From a population of 12,429 registered MSEs in Nairobi County (MSEA, 2024), a representative sample of 387 MSEs was chosen using multistage random sampling. Structured questionnaires were used for data collecting; a pilot test was carried out to guarantee dependability and validity. SPSS version 27 was used to examine quantitative data. While inferential analysis used several regression and correlation methods to assess hypotheses at a 95% confidence level (p < 0.05), descriptive statistics including means and standard deviations were computed. Findings: The analysis revealed strong positive correlations between distribution strategies and microinsurance uptake (r = 0.570), significant at p < 0.01. Regression models showed that the distribution strategy accounted for 32.5% of the variance in microinsurance uptake. The ANOVA results indicate an F-statistic of 144.547 with a p-value of 0.000 further suggesting that the relationship between distribution strategy and microinsurance uptake was statistically significant at the 95% confidence level. The unstandardized coefficient (B) for distribution strategy was 0.444, indicating that a one-unit increase in distribution strategy led to 0.444 units increase in microinsurance uptake. Unique Contribution to Theory, Practice and Policy: The study recommended that insurers need to expand and diversify distribution channels to enhance reach and accessibility among MSEs. In addition to traditional agents and brokers, mobile-based platforms, digital apps, and partnerships with mobile network operators should be prioritized to enhance distribution of microinsurance.